Fall Risk and Avoidance Behavior Due to Fear of Falling in Elderly Nursing Home Residents - Türen, Sevda; ÖZÇALIK, CENNET KARA; YILDIZ, GÜLİŞAN; TEKİR, MERYEM İREM (Rzeszow University Press, 2025)
Introduction and aim. Falls in the elderly affect their daily activities, causing a decrease in their quality of life and may even lead to death. This study aims to examine the risk of falling and the relationship between fear of falling and avoidance behaviors in elderly nursing home residents. Material and methods. Data were obtained using the “Fall Risk Assessment Scale (FRAS)” and the “Fear of Falling Avoidance Behavior Questionnaire (FFABQ)”. Results. The average age of the participants was 70.70±5.23 years. Total mean scores of FRAS and FFABQ were significantly higher in participants who could partially meet their daily needs on their own, had chronic diseases, used continuous medication, had problems with walking or balance, had vision or hearing problems, used walking aids, had fear of falling, and had experienced falls in the last three months. It was found that their average was significantly higher. It was determined that there was a strong and significant positive relationship between the FRAS and FFABQ total score averages. Conclusion. It was determined that elderly residents of nursing homes have a high risk of falling and that increased risk is associated with an increase in avoidance behaviors due to fear of falling.
Keywords: Elderly; Fall Risk; Fear of Falling